Recent Decrease of Summer Sea Ice in the Weddell Sea, Antarctica. Issue 11 (8th June 2020) - Turner, John; Guarino, Maria Vittoria; Arnatt, Jack; Jena, Babula; Marshall, Gareth J.; Phillips, Tony; Bajish, C. C.; Clem, Kyle; Wang, Zhaomin; Andersson, Tom; Murphy, Eugene J.; Cavanagh, Rachel
Abstract: In Austral summer 2016/2017, the sea ice extent (SIE) in the Weddell Sea dropped to a near‐record value in the satellite era (1.88 × 10 6 km 2 ), a large negative seasonal anomaly that persisted in an unprecedented fashion for the following three summers. Various atmospheric and oceanic factors played a part in the change. Ice loss started in September 2016 when the northern Weddell Sea experienced westerly winds of record strength, advecting multiyear sea ice from the region. In late 2016, a polynya over Maud Rise contributed to low SIE over the eastern Weddell Sea. With extensive areas of open water early in the summer, upper ocean temperatures increased by 0.5°C, with the anomalies persisting in subsequent years. The reappearance of the Maud Rise polynya in 2017, high ocean temperatures, and storms of record depth kept the summer SIE low. Plain Language Summary: Sea ice is an extremely important part of the Antarctic environment, providing an essential habitat for seals, seabirds, and Antarctic krill. It also caps the ocean, strongly influencing the transfer of heat from the relatively warm ocean into the frigid Antarctic atmosphere. In addition, it affects the ocean circulation through the release of salt when ice grows. In 2016/2017, the extent of summer sea ice in the Weddell Sea, Antarctica, dropped to a near‐record level in the satellite era, which starts in late 1978. The ice loss was in part caused by the reappearance of the Maud Rise polynya, an area of open water within the main area of pack ice. The ice‐free conditions allowed more energy from the Sun to be absorbed by the ocean, with the higher ocean temperatures persisting in subsequent years and slowing the formation of new ice. In parallel, westerly winds of record strength carried sea ice out of the region, so that the summer sea ice extent in the Weddell Sea is now 1, 000, 000 km 2 less than in 2013/2014. Key Points: Summer sea ice in the Weddell Sea, Antarctica decreased to a near‐record low extent in 2016/2017 and has subsequently remained low Westerly winds of record strength and the reappearance of the Maud Rise polynya were significant factors in the change in ice conditions The Weddell Sea summer ice extent is now 1, 000, 000 km 2 less than in 2013/2014